Diversity of Sulfated Polysaccharides From Cell Walls of Coenocytic Green Algae and Their Structural Relationships in View of Green Algal Evolution - Ciancia, Marina; Fernández, Paula Virginia; Leliaert, Frederik (Frontiers in Plant Science, 2020)
Seaweeds biosynthesize sulfated polysaccharides as key components of their cell walls. These polysaccharides are potentially interesting as biologically active compounds. Green macroalgae of the class Ulvophyceae comprise sulfated polysaccharides with great structural differences regarding the monosaccharide constituents, linearity of their backbones, and presence of other acidic substituents in their structure, including uronic acid residues and pyruvic acid. These structures have been thoroughly studied in the Ulvales and Ulotrichales, but only more recently have they been investigated with some detail in ulvophytes with giant multinucleate (coenocytic) cells, including the siphonous Bryopsidales and Dasycladales, and the siphonocladous Cladophorales. An early classification of these structurally heterogeneous polysaccharides was based on the presence of uronic acid residues in these molecules. In agreement with this classification based on chemical structures, sulfated polysaccharides of the orders Bryopsidales and Cladophorales fall in the same group, in which this acidic component is absent, or only present in very low quantities. The cell walls of Dasycladales have been less studied, and it remains unclear if they comprise sulfated polysaccharides of both types. Although in the Bryopsidales and Cladophorales the most important sulfated polysaccharides are arabinans and galactans (or arabinogalactans), their major structures are very different. The Bryopsidales produce sulfated pyruvylated 3-linked -D-galactans, in most cases, with ramifications on C6. For some species, linear sulfated pyranosic -L-arabinans have been described. In the Cladophorales, also sulfated pyranosic -L-arabinans have been found, but 4-linked and highly substituted with side chains. These differences are consistent with recent molecular phylogenetic analyses, which indicate that the Bryopsidales and Cladophorales are distantly related. In addition, some of the Bryopsidales also biosynthesize other sulfated polysaccharides, i.e. sulfated mannans and sulfated rhamnans. The presence of sulfate groups as a distinctive characteristic of these biopolymers has been related to their adaptation to the marine environment. However, it has been shown that some freshwater algae from the Cladophorales also produce sulfated polysaccharides. In this review, structures of sulfated polysaccharides from bryopsidalean, dasycladalean, and cladophoralean green algae studied until now are described and analyzed based on current phylogenetic understanding, with the aim of unveiling the important knowledge gaps that still exist.